Business model innovation of German VET service providers in international contexts – a longitudinal survey - Meyne, Lisa [Verfasser]; Kühn, Ida Kristina [Verfasser] (My University, 2025)
„To support German VET providers in their internationalisation, the Federal Ministry of Education and Research (BMBF) has created two funding programs ‘Vocational Training Export’ (BEX; 2010–2017) and ‘Internationalisation of Vocational Education’ (IBB; 2017–2022) for the development of international business models in VET. In this paper, innovations of the business models of the projects are analysed in order to find out the extent to which the innovations have occurred. The sample includes all funded projects (18), in which a minimum of one organisation was funded subsequently in both funding programs. The data includes project documents and qualitative interviews with project actors. In order to identify the business model innovativeness of the projects, a model by Taran, Boer, and Lindgren is used and extended by a further dimension (system) according to Bronfenbrenner and Kell. The data shows that nearly all projects innovate in several areas of the business model. While these are mainly incremental in nature in BEX, radical innovations dominate among the IBB projects. Among other things, it is also evident that the BEX projects with their innovations relate primarily to the meso level (institutions), while the IBB projects address more strongly the exo level (societal subsystems) with their novelties.“ (authors’ abstract; BIBB-Doku)
Keywords: I 1 Internationale Berufsbildung; 370; Berufsbildung; Internationalisierung; Internationale Zusammenarbeit; Bildungsexport; Projekt; Geschäftsmodell; Innovation